Entanglement of identical particles and the detection process. Issue 2 (18th June 2012) - Tichy, M.C.; de Melo, F.; Kuś, M.; Mintert, F.; Buchleitner, A.; Bird, J.; Kaiser, R.; Rotter, I.; Wunner, G.
Abstract We introduce detector‐level entanglement, a unified entanglement concept for identical particles that takes into account the possible deletion of many‐particle which‐way information through the detection process. The concept implies a measure for the effective indistinguishability of the particles, which is controlled by the measurement setup and which quantifies the extent to which the (anti‐)symmetrization of the wave‐function impacts on physical observables. Initially indistinguishable particles can gain or loose entanglement on their transition to distinguishability, and their quantum statistical behavior depends on their initial entanglement. Our results show that entanglement cannot be attributed to a state of identical particles alone, but that the detection process has to be incorporated in the analysis.